Research Of The Trend In The Piano Training And The Music Knowledge In China From The 20th To The 21st Century, Including A Concentrating On Guang XI Province As A Case Study - Yun, Bai; Ali, Lubna (Journal of Neonatal Surgery, 2025)
In recent years, gamification has become an integral part of both conventional classroom teaching and online learning settings at all educational levels. Due to the good impacts on student motivation and the effectiveness of the learning process, gamification methods are being used more and more by educational institutions. To facilitate the integration of digital games into the learning-teaching process, this paper presents a game-based teaching-learning environment. The emphasis on practical experience makes this environment perfect for online accounting skill development. The article's game-based virtual classroom has been successfully implemented for many years, and the quantity of students actively participating in class has been steadily increasing, all because gamification is gaining popularity at the university level.